Territorial Conflicts in (neo) extractivist advance contexts: the Campana Mahuida mining project case in the province of Neuquén (Huellas, 2016)
In Neuquén province, important oilfields, gas and mining sites are located. Although hydrocarbons remain central as part of economic development, nowadays the mining industry became a strong business vector, as it happens in the rest ofArgentina.In this respect, the exploitation of the underground resources is an attribution that the State ofNeuquéngrants to individuals and it has been regulated by laws and administrative provisions, none of which recognizes the right to the previous consultation to the Mapuche communities who live within the exploited territories. The consequence of this situation is an increasing number of conflicts between the communities and the State ofNeuquénas province, in different areas of the territory where the extractive activities try to advance.The particular case that is analyzed in this paper refers to a conflict in which a Mapuche community resisted the settlement of a mining corporation of Chinese origin in their territories. Even though the project was finally dismissed in the middle of a legal controversy after a provincial referendum that rejected this development, a whole process of conflicts and disputes between local actors took place. For some of them the project meant “the beginning of a new dignified life with a job" whereas for others the project was synonymous with “invasion, destruction and pollution”.
Keywords: territory; Mapuche community; mega mining development